Changes in the physiological activity of soybean (Glycine max L. Merr.) under the influence of exogenous growth regulators - Anna Nowak; Jacek Wróbel (Acta Agrobotanica, 2015)
In a two-year pot experiment (2008–2009) conducted at the Vegetation Hall, West Pomeranian University of Technology in Szczecin, we investigated the influence of exogenous growth regulators, i.e. indole-3-butyric acid (IBA) and 6-benzylaminopurine (BAP) and their mixture, on the activity of gas exchange and selected physiological features of soybeans (Glycine max L. Merr.). The experimental factors included the following Polish soybean cultivars: ‘Aldana’, ‘Progres’ and ‘Jutro’. During plant growth, CO2 assimilation (A), transpiration rate (E), stomatal conductance (gs), and substomatal CO2 concentration (ci) were determined. Two soybean cultivars, i.e. ‘Jutro’ and ‘Progres’, showed a significant increase in the intensity of assimilation and transpiration after using all kinds of growth regulators as compared with the control plants. It was found that the ‘Jutro’ cultivar, after using a mixture of growth regulators (IBA + BAP), was characterized by the significantly highest CO2 assimilation (A) and transpiration (E) as well as the highest stomatal conductance (gs). The ‘Aldana’ cultivar, on the other hand, responded by a significant reduction in the transpiration rate, stomatal conductance and subsomatal CO2 concentration. The spraying of the plants with exogenous growth regulators had a significant influence on the increase in the number of stomata and stomatal pore length, mostly on the lower epidermis of the lamina. It was also found that plants from the ‘Jutro’ and ‘Aldana’ cultivars sprayed with IBA and IBA + BAP were characterized by the highest yield, as compared with the control plants. In the case of the ‘Jutro’ cultivar, after using the growth regulators, a positive correlation was observed between the assimilation and transpiration rates and the length of stomata, which in consequence produced increased yields.